Muscle fiber characteristics and performance correlates of male Olympic-style weightlifters - Fry, A. C.; Schilling, B. K.; Staron, R. S.; Hagerman, F. C.; Hikida, R. S.; Thrush, J. T. (The Journal of Strength and Conditioning Research, 2003)
Biopsies from the vastus lateralis muscle of male weightlifters (WL; n = 6; ± SE, age = 27.0 ± 2.1 years), and non-weight-trained men (CON; n = 7; age = 22.0 ± 2.0) were compared for fiber types, myosin heavy chain (MHC) and titin content, and fiber type-specific capillary density. Differences (p < 0.05) were observed for percent fiber types IIC (WL = 0.4 ± 0.2, CON = 2.4 ± 0.8); IIA (WL = 50.5 ± 3.2, CON = 26.9 ± 3.7); and IIB (WL = 1.7 ± 1.4, CON = 21.0 ± 5.3), as well as percent MHC IIa (WL = 65.3 ± 2.4, CON = 52.1 ± 4.2) and percent MHC IIb (WL = 0.9 ± 0.9, CON = 18.2 ± 6.1). All WL exhibited only the titin-1 isoform. Capillary density (caps·mm2) for all fiber types combined was greater for the CON subjects (WL = 192.7 ± 17.3; CON = 262.9 ± 26.3), due primarily to a greater capillary density in the IIA fibers. Weightlifting performances and vertical jump power were correlated with type II fiber characteristics. These results suggest that successful weightlifting performance is not dependent on IIB fibers, and that weightlifters exhibit large percentages of type IIA muscle fibers and MHC IIa isoform content.